A Retrospective Study of Soft Tissue Tumors - Role of Histomorphology in Diagnosis - Damani, Sagar Sanjay; Patil, Soniya Anant; Ansari, M H; Baste, Balaji Devrao (Annals of Pathology and Laboratory Medicine, 2020)
Background: The field of soft tissue tumors is vast and yet to be explored. The diagnosis of these tumors is always challenging for the pathologists. The overlap in the clinical and radiological features makes histopathology very crucial in their identification. Methods: This is a retrospective study of soft tissue tumors over a period of 18 months from January 2014 to June 2015 conducted in the Department of Pathology. The gross specimens were fixed in 10% formalin and the slides were stained by Hematoxylin and Eosin. Immunohistochemistry was performed wherever necessary. Result: A total of 235 soft tissue tumors were studied of which benign cases were 225 (95.75%), intermediate 04 (1.70%) and malignant 06 (2.55%). The tumors had a male preponderance, with majority in the third decade, predominantly occurring in the head neck region. Of a total of eleven categories of soft tissue tumors in our study, the adipocytic category was the most common followed by the nerve sheath and vascular tumors. Conclusion: Molecular diagnosis have started to gain momentum in the field of soft tissue tumors, however histomorphology still remains the gold standard.